Design of a transport robot in an industrial environment - خنيسي, محمد (Latakia University Journal -Engineering Sciences Series, 2025)
Designing a transport robot in an industrial environment represents an important step towards achieving full automation in factories. By integrating modern technology into industrial processes, productivity can be improved, safety can be enhanced, and the burden on workers can be reduced. This work deals with the design of a transport robot dedicated to working in industrial environments, aiming to improve efficiency and reduce costs in transportation and storage operations. The main objective of designing the robot is to develop a system capable of moving independently and interacting with different elements in the industrial environment, such as machines, equipment, and employees. In this research, a model of a robot is presented that is controlled in two ways: the first is using image processing, where the path is drawn by the computer and an algorithm is applied to determine the path coordinates, then the path coordinates are sent to the robot, which walks along a specific path, sending a message informing the user in the event of an obstacle. The second method involves the robot searching for an object of a specific color that is determined by the user and gives an alarm signal in the event of the object's presence. In the first part of this work, the robot was designed and programmed using the computer, and in the second part of the work, the robot was designed in real form and its correct operation was verified. The robot was tested in different working conditions and its work was verified accurately as planned.